Campylobacter coli infection in pet birds in southern Italy. Issue 1 (December 2017) - Dipineto, Ludovico; Borrelli, Luca; Pace, Antonino; Romano, Violante; D'Orazio, Stefano; Varriale, Lorena; Russo, Tamara; Fioretti, Alessandro
Abstract Avian species are considered as the main reservoir ofCampylobacter spp. However, few data are available on the presence of this microorganism in pet birds. This study was therefore performed to determine the prevalence ofCampylobacter spp. in pet birds bred in southern Italy. Faecal samples were collected from 88 cages housing different species of pet birds and examined by bacteriological culture and polymerase chain reaction. A total of 13.6% of the cage samples were positive forCampylobacter coli . OtherCampylobacter spp. were not found. The study shows thatC. coli can be isolated from the cages of apparently healthy pet birds, which should therefore be considered as potential carriers ofC. coli and a possible source of infection for humans and companion animals.